1999
DOI: 10.4049/jimmunol.162.2.1064
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 Is a Heparin-Binding Cytokine

Abstract: Using an ELISA approach, we demonstrate that recombinant human IL-12 (rhIL-12) binds strongly to an immobilized heparin-BSA complex. This binding is completely displaceable with soluble heparin, IC50∼ 0.1 μg/ml, corresponding to ∼ 10 nM. By interpolation with our previous findings, this indicates an affinity for heparin greater than that of antithrombin III and comparable with that of FGF-2, two high-affinity heparin-binding proteins. Recombinant murine IL-12 also binds strongly to heparin. The binding of rhIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(13 citation statements)
references
References 39 publications
5
8
0
Order By: Relevance
“…The interaction between heparin and glycosaminoglycan in cytokines has received significant attention in recent years. [68,69] Heparin binds to the p40 subunit of IL-12, [70] which is a crucial protein in Th17 differentiation. [71] Additionally, INF-𝛾 has a heparin-binding site.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between heparin and glycosaminoglycan in cytokines has received significant attention in recent years. [68,69] Heparin binds to the p40 subunit of IL-12, [70] which is a crucial protein in Th17 differentiation. [71] Additionally, INF-𝛾 has a heparin-binding site.…”
Section: Discussionmentioning
confidence: 99%
“…GAG binding can also protect the cytokine from proteolytic degradation, as has been shown for basic and acidic FGF [41], IL-6 [42], IL-7 [38], IFN-γ [43]; and/or can facilitate the local accumulation of the cytokine as has been described for IL-2 [44] and IL-6 [42]. The possibility that IL-12 has heparin-binding activity was first proposed by Wolf et al [3], and this activity was found by Hasan et al [45], reporting high affinity binding of IL-12 to heparin/heparan sulfate. This latter group and more recently, Jayanthi et al and Garnier et al suggested that the heparin-binding activity of human and mouse IL-12 involves a cluster of basic amino acids within the C-terminal domain of the p40 subunit of human and mouse IL-12 [45][46][47].…”
Section: Introductionmentioning
confidence: 91%
“…The possibility that IL-12 has heparin-binding activity was first proposed by Wolf et al [3], and this activity was found by Hasan et al [45], reporting high affinity binding of IL-12 to heparin/heparan sulfate. This latter group and more recently, Jayanthi et al and Garnier et al suggested that the heparin-binding activity of human and mouse IL-12 involves a cluster of basic amino acids within the C-terminal domain of the p40 subunit of human and mouse IL-12 [45][46][47].…”
Section: Introductionmentioning
confidence: 95%
“…ECM‐based retention is a promising strategy for anchoring cytokines due to the overexpression of, for example, collagen in solid tumors 113,114 . Furthermore, this strategy is actually biomimetic, as numerous cytokines (e.g., IL‐2, 22 IFNɣ, 115 and IL‐12 116 ) exhibit strong ECM interactions that keep their endogenous effects localized. Momin et al reported on a collagen‐anchoring platform that leverages these intratumoral collagen reserves for enhanced cytokine retention 24 .…”
Section: Spatial Programming By Intratumoral Administration and Ancho...mentioning
confidence: 99%